Pengaruh Penambahan Stabilizer Carboxyl Metyl Celulosa dan Tepung Agar terhadap Karakteristik Fisiko Kimia Velva Sirsak - Putri , Gustiarini Rika; Samah , Selfa Dewati (Politeknik ATI Padang, 2021)
Fruits are perishable agro materials, so further processing is necessary after the fruit is harvest. Soursop is a fruit dessert with characteristics like ice cream. The purpose of this study was determined the appropriate compotition and agar powder in the manufacture of soursop velva so that a product with physical characteristics such as ice cream. The physical characteristics of soursop velva are total solid, water content, pH, vitamin C, fiber, total acid, melting speed and overrun. The soursop velva research method with six treatments, A (0,4 % CMC added), B (0,5% CMC added), C (0,6% CMC added), D (0,4% agar powder added), E (0,5% agar powder added), F (0,6% agar powder added). Observation were made on the physico-chemical characteristics of soursop velva. The result shows that soursop Velva added with 0,6% agar powder content 24,79% total solid, 75,24% water content, pH 4,30 and 33, 84 mg/100 g material of vitamin C, 2,2% fiber, 2,2% total acid, with 19,69 minutes melting speed and 134,67% overrun.